Filogenia e biogeografia de Leptohyphidae (Insecta: Ephemeroptera) - Souto, Paula Malaquias (2018)
Leptohyphidae is a Pan-American mayfly family with 163 species divided into 15 genera. It belongs to the infraorder Pannota, where it was already considered a subfamily of Tricorythidae. However, there is no agreement among researchers as to how exactly pannotan families are related, specially conserning to leptohyphid sister group. Among the families proposed as more related to Leptohyphidae, Tricorythidae and Coryphoridae are two examples. Being the first restricted to the African continent and the second endemic of the Amazon, the two relationships suggest different biogeographic proposals for the origin and evolution of Leptohyphidae. Within this context, the present dissertation presents two studies within Leptohyphidae: one about the genetic diversity of a possible cryptic species with eye color variation, Leptohyphodes inanis; and another investigating the phylogenetic relationships of Leptohyphidae with other pannotan families, as well as the relationships between genera within the family and the possible processes that contributed to the current distribution pattern of Leptohyphidae genera. To assess genetic differences among populations and relate them to the colour variation of the eyes, we sequenced a segment of the mitochondrial COI gene from 17 individuals from different populations with two colours variations: red and black. All analyses (Bayesian Inference, Neighbor Joining and haplotype network) found three independently highly supported evolutionary lineages, each one mostly restricted to a Southeastern Brazil mountain range. However, Pairwise divergences modelled by Kimura-2 parameter showed high values of intraspecific genetic divergence (0 to 30.5%), with 23.3 to 24.9% between lineages and 4 to 13% within lineages, providing strong evidence of at least three putative species in the L. inanis species complex. In addition, red eyes were recovered as plesiomorphic traits in the group and not a good diagnostic to identify the species. About the second study, the analyses were made based on molecular and morphological characters using Bayesian and parsimony approaches. All analyses recovered the monophyly of the family, whereas the Leptohyphidae sister group varied according to the method, such as Teloganodidae (Afrotropical), Ephemerythidae (Afrotropical) or a clade formed by Melanemerellidae + Coryphoridae + Teloganodidae (Atlantic Forest, Amazonian and Afrotropical, respectively). Based on S-DIVA and divergence time estimation analyses, ancestral Leptohyphidae was found restricted to the Chacoan Subregion in South America after a vicariant event of the Gondwana continent, around 151.9 Mya (120.0 - 184.4). Furthermore, as result three new species were described, two belonging to Macunahyphes and one to Tricorythodes.